2011
DOI: 10.1051/fruits/2011034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a galactomannan coating on mango postharvest physicochemical quality parameters and physiology

Abstract: --Introduction. Films act as semi-permeable gaseous barriers capable of maintaining fruit postharvest quality; thus coatings consisting of non-traditional sources may represent an alternative tool for producers. The objective of our work was to investigate the effect of a galactomannan coating on postharvest quality and physiology of 'Tommy Atkins' mangoes. Materials and methods. Physiologically mature mangoes were divided into four lots and stored for 16 d. Control uncoated fruits (lot 1) were stored at ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
2
4
0
Order By: Relevance
“…However, on the seventh day of storage, a satisfactory result could also be observed for the treatments with ferulic acid. Since in this case, and as mention above, this result cannot be attributed, at all, to a high water content of the apples, the results suggest that the polysaccharide depolymerization involved in the increase of soluble solids content (Aguiar et al, 2011) may be most effectively controlled by the presence of ferulic acid.…”
Section: Effect Of the Selected Formulations On Firmness Ph And Solusupporting
confidence: 58%
“…However, on the seventh day of storage, a satisfactory result could also be observed for the treatments with ferulic acid. Since in this case, and as mention above, this result cannot be attributed, at all, to a high water content of the apples, the results suggest that the polysaccharide depolymerization involved in the increase of soluble solids content (Aguiar et al, 2011) may be most effectively controlled by the presence of ferulic acid.…”
Section: Effect Of the Selected Formulations On Firmness Ph And Solusupporting
confidence: 58%
“…Coating slowed the changes in pH and TA in banana fruit by effectively delaying fruit senescence, as reported by Gol and Rao [35]. Similar findings were obtained by Aguiar et al, who reported that mango fruit treated with galactomannan coating retained TA at a higher level as compared with uncoated samples [36].…”
Section: Changes In Titratable Acidity and Phsupporting
confidence: 83%
“…It is well known that the lower the respiration rate by means of postharvest applications, the lower the use of organic acids in the enzymatic reactions of respiration [13,17]. Aguiar et al also noted that a variety of coating materials have been investigated due to their ability to modify the internal fruit atmosphere, slowing down respiration and, therefore, ripening and senescence [18].…”
Section: Effect On Ph and Total Soluble Solidsmentioning
confidence: 99%